2016
DOI: 10.1016/j.jcte.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparing metabolic control and complications in type 2 diabetes in two Pacific Islands at baseline and following diabetes care intervention

Abstract: HighlightsGlycaemic control improved and mean HbA1c decreased significantly in study subjects.Mean blood pressure was reduced significantly in study subjects in the Solomon Islands.The percentage of subjects achieving recommended clinical targets increased.A trend towards lower complications rates of foot problem was observed.Effort to strengthen the quality and accessibility of diabetes care is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…For example, treatment for diabetes should be timely, focused on people centred integrated and self-management approach for better health outcomes, [23][24] and implementing a locally relevant and sustainable model of diabetes care focusing on capacity building in the small island states demonstrated improvement in diabetes services, metabolic and glycaemic control. 25 However, our study found a high prevalence of poor glycaemic control, high blood pressure and overweight and obese among people with diabetes, and irregular follow-up visits. This was most likely due to the lack of knowledge and awareness on diabetes complications, and disruption of diabetes management services resulting from COVID-19 pandemic and natural disasters affecting Tonga in recent years.…”
Section: Discussionmentioning
confidence: 49%
“…For example, treatment for diabetes should be timely, focused on people centred integrated and self-management approach for better health outcomes, [23][24] and implementing a locally relevant and sustainable model of diabetes care focusing on capacity building in the small island states demonstrated improvement in diabetes services, metabolic and glycaemic control. 25 However, our study found a high prevalence of poor glycaemic control, high blood pressure and overweight and obese among people with diabetes, and irregular follow-up visits. This was most likely due to the lack of knowledge and awareness on diabetes complications, and disruption of diabetes management services resulting from COVID-19 pandemic and natural disasters affecting Tonga in recent years.…”
Section: Discussionmentioning
confidence: 49%
“…Over the past two decades, research on T2DM in Pacific Island countries has mainly focused on influencing factors analysis [7,8], diabetes prevention strategies [9][10][11][12][13], ethnic differences in the incidence of diabetes in Pacific Island countries [14][15][16][17], the relationship between diabetes and other diseases7, and epidemiological research [18,19]. Some studies specifically highlight the importance of obesity and dietary changes in Pacific Island countries, both of which are thought to be major contributors to the increase in diabetes [7,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%